1H NMR based metabolic profiling of day 2 spent embryo media correlates with implantation potential. (February 2014) - Wallace, Martina; Cottell, Evelyn; Cullinane, Jennifer; McAuliffe, Fionnuala M.; Wingfield, Mary; Brennan, Lorraine
Abstract Morphological assessment is currently the primary technique for selection of viable embryos for uterine transfer during assisted reproductive techniques, however this method has limited predictive power. The objective of this study was to employ NMR based metabolic profiling analysis of spent embryo culture media to identify novel biomarkers of embryo viability and provide insight into the metabolism of a viable embryo. A total of 37 patients undergoing IVF/ICSI treatment were recruited and 58 media samples were collected from embryos that were transferred back to the uterus. 1H NMR spectra were acquired and analyzed resulting in the quantification of 12 metabolites in the media samples. Analysis of metabolite ratios revealed significant differences between those patients with positive (n = 27) and negative (n = 31) urinary βhCG results. Some of the most biologically relevant differences include a 17% increase in the formate to glycine ratio and a 22% decrease in the citrate to alanine ratio in the spent embryo media from the positive pregnancy group. Overall, the results indicate that metabolic profiling may provide a means of identifying biomarkers that aid selection of viable embryos.